Designed acute physical activity to benefit primary school children's cognition: Effects of cognitive challenge, bout duration and positive affect - Sofia Anzeneder; Valentin Benzing; Mirko Schmidt (Bern Open Publishing, 2023)
Introduction Acute bouts of physical activity (PA) have the potential to transiently enhance children's cognition (Ludyga et al., 2016). Although these positive results seem to be relatively consistent, there is considerable heterogeneity in the magnitude of effects (Lubans et al., 2022). Cognitive benefits are largely influenced by the interaction of quantitative and qualitative PA task characteristics (Lubans et al., 2022; Pesce, 2012), as well as by individual differences in responsiveness to PA bouts (Herold et al., 2021). Understanding the individual and joint effects of moderators is of great practical importance in the educational setting (Schmidt et al., 2021). This information could help to design and individualize PA breaks to enhance cognitive functions that are essential for learning and academic achievement, such as executive functions (EFs; responsible for self-regulation and goal-directed behavior) and attention (responsible for allocation of resources). Among PA task characteristics, the level of cognitive challenge has attracted increasing interest; however, a low comparability of PA studies varying in both quantitative parameters and qualitative modality do not allow for definitive conclusions (Paschen et al., 2019; Schmidt et al., 2021). Moreover, preliminary evidence highlights that positive affect induced by the PA bout may mediate PA effects on cognition (Schmidt et al., 2016). Thus, the aim of the research program was threefold: (1) shed light on which cognitive challenge level in acute PA may affect children's EFs and attention ("cognitive challenge" study); (2) investigate which bout duration of the identified optimal cognitive challenge level is necessary to reap largest benefits ("bout duration" study); and (3) manipulate positive affect through supportive feedback (and music) to elucidate its influence on cognitive performance ("positive affect" study). Methods Three studies with within-subjects experimental design were conducted with 5th-6th graders (N = 110, N = 114, N = 102; determined by a-priori power analyses). Each study used an exergame (i.e., active video game that involves gross-motor PA) as intervention, performed at 65% maximum heart rate (HR). For the studies, the following experimental conditions were used: • "Cognitive challenge" study: three sessions (15-min) with different cognitive challenge levels (low, mid, high), continuously adapted to the individual ongoing performance by an ascending number of distracting stimuli and misleading cues. • "Bout duration" study: four sessions with the same, individually adapted cognitive challenge level (chosen according to "cognitive challenge" study) and different PA durations (5-, 10-, 15-, 20-min). • "Positive affect" study: three sessions with the same cognitive challenge level and duration of the PA bout (chosen according to "cognitive challenge" and "bout duration" studies) and different affect-inducing feedback (no feedback, music with sound effects, music with sound effects and verbal supportive feedback). Each exergame session was performed individually during school hours (once a week). Children wore motion-based trackers and a HR sensor, while playing a virtual game that required performing different movements (e.g., jumps, squats, punches). During each session (every 5 minutes), perceived physical and cognitive challenge, as well as affective states were assessed. After the exergame, executive control (flanker effect), attentional alerting and orienting, and their interactive functioning were assessed by a child-adapted attention network test (ANT-R; Fan et al., 2009). Repeated measures ANOVAs were calculated to analyze intervention effects on reaction times (RTs) and accuracy data, with subsequent post-hoc Bonferroni-adjusted comparisons. Results "Cognitive challenge" study. A significant interaction for RTs between cognitive challenge and flanker conditions emerged [F(2, 100) = 4.16, p = .018, ƞ2p = .07], with no effects for accuracy. Post-hoc analyses of RT difference data (incongruent - congruent, i.e., flanker effect) revealed best performance after the high-challenge condition (ps < .045; ƞ2ps > .01). Regarding differential effects, adding sex to the model showed that it moderated the effect of cognitive challenge on the interactive functioning of executive control and attentional orienting [F(6, 96) = 2.33, p = .038, ƞ2p = .12]. "Bout duration" study. A significant effect of duration on overall RTs emerged [F(3, 101) = 4.04, p = .009, ƞ2p = .11], with no effects on accuracy. Post-hoc comparisons revealed significantly faster RTs after the 15-min compared to the 10-min condition (p = .019, ƞ2p = .09). Regarding differential effects, adding habitual PA level to the model showed that it moderated the effect of duration on the interactive functioning of executive control and attentional orienting [F(3, 100) = 4.81, p = .004, ƞ2p = .13]. "Positive affect" study. Ongoing - results will be presented at the SGS-meeting. Discussion The high-challenging bout benefited children's executive control the most ("cognitive challenge" study), supporting the hypothesis that PA designed to generate cognitive engagement may facilitate performance in subsequent EF tasks (i.e., cognitive stimulation hypothesis; Pesce, 2012). However, attentional alerting and orienting were unaffected in the current study, which is in line with the absence of effects found for aerobic PA bouts (van den Berg et al., 2018). The 15-min cognitively high-challenging bout benefited children's overall information processing speed the most, with no duration-dependent differences for executive control, alerting or orienting ("bout duration" study). Results extend to acute cognitively challenging PA the duration-dependent effects that have been found for acute high-intensity or aerobic PA bouts on overall information processing, but neither on EFs (Hatch et al., 2021), nor on alerting and orienting (van den Berg et al., 2018). Interestingly, in both "cognitive challenge" and "bout duration" studies an intriguing interplay between individual and tasks characteristics on the interactive functioning of executive control and orienting networks emerged. Indeed, the high-challenging bout benefited - for males only - also the efficiency of executive control under disadvantageous spatial attention conditions, consistent with previous adult studies without PA (Li et al., 2021). Whereas, the 15-min duration benefited the same interactive functioning for more active children only, which is in line with evidence that cognitively challenging PA bouts benefit EF efficiency more in children who are physically and cognitively better equipped to capitalize on it (Jäger et al., 2015). The added value of the present studies within an inconsistent evidence base (Paschen et al., 2019; Schmidt et al., 2021) is threefold. The studies allowed to (1) disentangle cognitive from physical challenge effects, while individualizing cognitive challenge; (2) identify the optimal duration for learning contexts; and (3) further the understanding of the interplay between individual and task characteristics. The "positive affect" study will complement the investigation of individual- and task-level moderators with information on positive affect as potential mediator for the acute PA-cognition relation. Results of the research program may inform the design of acute and chronic PA studies implemented in the school context, to capitalize jointly on physical and cognitive benefits of PA. References Fan, J., Gu, X., Guise, K. G., Liu, X., Fossella, J., Wang, H., & Posner, M. I. (2009). Testing the behavioral interaction and integration of attentional networks. Brain and Cognition, 70(2), 209-220. https://doi.org/10.1016/j.bandc.2009.02.002 Hatch, L. M., Dring, K. J., Williams, R. A., Sunderland, C., Nevill, M. E., & Cooper, S. B. (2021). Effect of differing durations of high-intensity intermittent activity on cognitive function in adolescents. International Journal of Environmental Research and Public Health, 18(21), Article 11594. https://doi.org/10.3390/ijerph182111594 Herold, F., Törpel, A., Hamacher, D., Budde, H., Zou, L., Strobach, T., Müller, N. G., & Gronwald, T. (2021).